Zwischen Anspruch und Wirklichkeit: Die sinkende Nachfrage nach Deutsch als Fremdsprache in Dänemark und Norwegen - Bauer, Karen; Lindemann, Beate (Linguistik Online, 2025)
This study investigates the situation of German language education in Denmark and Norway. The focus is on the causes of declining interest and the measures taken by educational authorities to promote German language skills. The research addresses the measures proposed and recommended by national educational authorities, how such measures are implemented in educational institutions, and how well these measures are known and applied by local experts, such as German teachers and employees in the field of German language education/teacher education at colleges and universities. This study employed an online survey methodology to examine German language education in Denmark and Norway. More than 400 teachers and 40 employees from universities and colleges responded to the survey. Qualitative content analysis was then applied to the resulting data. The findings reveal a clear discrepancy in the practical application of governmental documents within school and higher education settings. The study suggests provision of specific German language curricula, ongoing teacher training, and sustained funding for innovative language education practices. It emphasizes the need for practical implementation of government strategies and long-term support for educational initiatives.